Cell Adhesion Mediated by VCAM–ITGα9 Interactions Enables Lymphatic Development. Issue 5 (May 2015) - Yang, Yiqing; Enis, David; Zheng, Hui; Chia, Stephanie; Yang, Jisheng; Chen, Mei; Dhillon, Veerpal; Papayannapoulou, Thalia; Kahn, Mark L.
<x xml:space="preserve">Abstract</x> Objective— Adhesive ligand–receptor interactions play key roles in blood vessel angiogenesis but remain poorly characterized during lymphatic vessel growth. In this study, we use genetic approaches in both fish and mice to address the roles of cell surface integrin ligand vascular cell adhesion molecule (VCAM) and its 2 receptors, integrins α9 and α4, during lymphatic vascular development. Approach and Results— Conditional deletion of the Vcam gene was used to test VCAM function in lymphatic growth in midgestation mice. Morpholino knockdown and cRNA rescue of the 2 zebrafish vcam alleles, as well as integrins α9 and 4, were used to test the role of these ligands and receptors during lymphatic growth in the developing fish. We show that VCAM is essential for lymphatic development in the zebrafish embryo and that integrin α9 (Itgα9) rather than Itgα4 is the required VCAM receptor in the developing fish. VCAM is expressed along lines of lymphatic migration in the mouse intestine, but its loss only retards lymphatic growth. Conclusions— These studies reveal an unexpected role for cell–cell adhesion mediated by Itgα9–VCAM interactions during lymphatic development in the fish but not in the mouse. We propose that the relative importance of cellular adhesive ligands is magnified under conditions of rapid tissue growth when the cell number increases faster than cell matrix, such as in the early zebrafish embryo.